History of King Philip, sovereign chief of the Wampanoags - Abbott, John S. C. (John Stevens Cabot), 1805-1877 (Online access with subscription: Proquest Ebook Central., 2001)
Metacomet, younger son of Massasoit of the Wampanoags, was also known as King Philip. In 1662 he succeeded his brother, Wamsutta, as sachem or chief of the Wampanoag Indian tribe. Metacomet eamestly attempted to maintain his father's peaceful policies with the Colonists, but the English pushed ever farther into Wampanoag lands, imposing their laws on the native people.